DISTRIBUSI KONSUMSI PANGAN ANTAR ANGGOTA RUMAH TANGGA PADA SAAT KRISIS EKONOMI DI DUA DESA IDT KABUPATEN SUBANG - Sri Prihatini; Syafrudin Syafrudin; Vita Kartika; Herman Sudiman (Persagi, 1999)
The Distribution Food Consumption Among The Family Members at Economic Crisis In Two IDT Villages In Subang District.The economic crisis in Indonesia has decreased the purchasing power of the families which further affected the household food consumption. The objective of this study is to observe the effect of economic crises on the intra-household food distribution, particularly the poor families. In other words, the objective of the study is to identify which of the family members that affected most by the crises. The socioeconomic status and food consumption data was collected from 100 households in two poor villages in the district of Subang, West Java. There were two rounds of data collection. The first data collection was carried out in August 1998 to represent the